Methods for coating solid-phase microextraction fibers with carbon nanotubes - Ghaemi, Ferial; Amiri, Amirhassan; Yunus, Robiah (Elsevier, 2014)
The presence of carbon nanotubes (CNTs) on the surfaces of solid-phase microextraction (SPME) fibers can enhance the efficiency of the extraction. Their unique properties, such as large surface area, and excellent chemical, mechanical and thermal stability, make such fibers very attractive as adsorbents in SPME. The current review concentrates on the different coating methods, such as chemical bonding, physical attachment, sol–gel technique, electrochemical deposition and electrophoretic deposition (EPD) that coat the SPME fibers with CNTs. We also briefly discuss the advantages and the disadvantages of these coating methods.